PELATIHAN DAN PENDAMPINGAN PEMBUATAN PUPUK ORGANIK BERBASIS MIKROORGANISME SEBAGAI IMPLEMENTASI PEMBELAJARAN IPA (BIOLOGI) DI SMP NEGERI 11 DENPASAR - I Wayan Suanda; I Gusti Ayu Rai; Kadek Intan Rusmayanthi; I Ketut Widnyana (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
Training and assistance in making organic fertilizer from microorganism-based organic materials was carried out at SMP Negeri 11 Denpasar. This training and assistance in making organic fertilizer is a work program from SMP Negeri 11 Denpasar in collaboration with the community service team from PGRI Mahadewa University Indonesia. Making organic fertilizer through composting activities is one of various methods of processing organic waste which aims to reduce and also change the composition of waste into products that are useful in life. Waste produced in life activities from organic materials and plant leaf waste produced in school gardens can be processed into organic fertilizer by using microorganisms as activators. The students who carried out this organic fertilizer making activity were welcomed enthusiastically, there was a sense of curiosity, cooperation and high enthusiasm because it was related to science learning at school and their daily lives.